Mexico's "war" on drugs: causes and consequences - Toro, María C. (Studies on the impact of the illegal drug trade, 1995)
"Reminds readers that Mexico, a country with a relatively low level of domestic drug abuse, spends 'substantial' portions of its police and military budgets combating drug traffic. All-too-brief overview of Mexico's drug market and anti-drug policies"--Handbook of Latin American Studies, v. 57